Providing digital identity and academic attributes through European eID infrastructures: Results achieved, limitations, and future steps. (6th August 2019) - Berbecaru, Diana; Lioy, Antonio; Cameroni, Cesare
Summary: Electronic identity is getting an increased importance nowadays since relentless digitalization and 24/7 connectivity continue to transform everyday life. To support the recognition of electronic identification cross‐border within the European Union, the European Commission (EC) released the eIDAS Regulation, which became effective on September 2018. To put eIDAS in practice, the EC has supported the definition of the technical specification; it provides a sample implementation; and it coordinates the eIDAS Network composed of eIDAS nodes of various countries. Each eIDAS node has a generic part required for the communication with the other nodes, and a specific part that each country has to modify independently according to its legal, operational, and technical requirements. Although this specific part is very important because it affects the node flexibility and the interaction with the other actors at the national level, it is less known in practice. We describe the adaptation of this specific part in Italy to perform authentication and provision of attributes through the STORK and STORK 2.0 infrastructures (the predecessors of eIDAS), based on our experience in the homonym projects. Significant effort is spent currently to build real services exploiting the eIDAS infrastructure, eg, the eID4U project proposes eIDAS node extension with new attributes required by some common academic services, such as student registration at a foreign university. We describe the support for these new attributes in the eIDAS nodes and the modification of the specific part of the Italian eIDAS node to allow attributes retrieval from different authorities.